Designing an ATmega328 Microcontroller Based Gesture-controlled IoT UGV Unit and Creating a Camera System Using Linux Distribution - Krucsó, László; Erdei, Timotei István; Kapusi, Tibor Péter; Husi, Géza (Recent Innovations in Mechatronics, 2019)
The topic of the research is the design and building of a UGV (Unmanned Ground Vehicle), which we can control wirelessly with a glove designed for this purpose. The design and use of this gesture-controlled robot can be observed in this summary. A camera will be installed on the robot unit, whose image we can query through the local network. Furthermore, the hardware and software for this camera system will be described as well.